Prevalence, treatment-seeking behavior, and cost of Headaches: a descriptive study from Iran - Amin, Rozhin; Shafiee, Sepehr; Sohrabi, Mohammad-Reza (Social Determinants of Health, 2023)
Background: This study was conducted with the intention of evaluating the prevalence of headache disorders in Tehran, assessing medical seeking behavior and costs endured by individuals affected, and compare them between men and women. Method: A cross-sectional study was conducted including individuals aged 18 and older from general population of Tehran through stratified random sampling method. Information on demographic characteristics, headache features, medical help seeking behaviors, medications used, and economic cost endured were collected through a self-administered structured questionnaire. The characteristics of the study population were presented using descriptive analysis. Chi-squared test and Independent T test were performed to compare the variables between sexes. Result: Data on 523 adult participants were analyzed. Main findings showed a prevalence of 96% for all headaches in adults, including 47.9 % (n = 241) women and 52.1% (n = 262) men. Mostly described their headache as a squeezing sensation (32.8 %) felt bilaterally (78%) with medium intensity (59%). About a third (31%) reported reduced productivity due to headache. The prevalence of self-treatment was 75% in study population and about two third reported using medications for acute treatment of headache. Mean± SD out of pocket payment of US139 ± 114.6, and average monthly expenditure of US4.1 ± 13.4 for headache management purposes were documented. No significant differences were found between the sexes in terms of headache features, treatment-seeking behaviors, and headache management expenditures. Conclusion: Findings point to the importance of prioritizing headache disorders in future decision-making and resource allocation strategies.